The sale of medicines used for diabetes mellitus treatment in retail segment of Russian pharmaceutical market - I. K. Petrukhina; A. M. Lazarev; T. K. Ryazanova; P. A. Lebedev; E. P. Gladunova; G. T. Glembotskaya (Фармакоэкономика)
Objective: to study the characteristics of the population consumption of medicines for the treatment of diabetes mellitus (DM), sold in the retail sector of the pharmaceutical market of the Russian Federation (RF).Material and methods. The study analyzed data on products assortment and sales volumes for drugs used to treat DM (according to Anatomical Therapeutic Chemical (ATС) classification) through pharmacies in all federal districts of the RF for the period 2020–2023. In particular, the following ATС groups were studied: A10A, A10B, H04AA and A16AX (thioctic acid), as well as “sibutramine + metformin” combination prescribed to correct obesity in DM patients. The results were obtained on basis of comparative, retrospective, logical, and graphical methods as well as content analysis, data grouping in accordance with ATС groups, and descriptive statistics.Results. In the retail sector of the pharmaceutical market of the RF, 54.9 million packages of antidiabetic drugs were sold for 32.4 billion rubles from 2020 to 2023. In the structure of sales in monetary terms, the share of Russian-manufactured drugs amounted to 16–17% approximately, and in physical terms, i.e. by the number of packages, it reached 37–39%. Throughout the analyzed period, the weighted average price (WAP) per 1 package of a drug for DM treatment increased from 472 to 589 rubles. Concurrently, as of year-end 2023, WAP per 1 package of an imported drug was 3 times higher than WAP of a domestic drug (784 and 259 rubles, respectively). In 2023, more than 45% of pharmacy sales in physical terms accrued to drugs of the ATC subgroup A10BA Biguanides (metformin), and about 25% to A10BB Sulfonylurea derivatives (glibenclamide, gliclazide, glimepiride, etc.). In 2023, the highest sales in monetary terms accrued to methsopamine, daphgylflozin, tytochotic acid, empagliflozin and gliclazide. In the structure of retail sales of drugs for DM treatment, fixed combinations accounted for about 15%. Despite an increase in the number of trade names of fixed combinations (from 24 in 2020 to 30 in 2023), their share in the product assortment structure remained insignificant, that did not comply with international recommendations for DM treatment.Conclusion. Using pharmacoepidemiological monitoring tools, the features of the population consumption of drugs prescribed for DM treatment in the retail sector of the pharmaceutical market of the RF were studied in a retrospective aspect (for the period from 2020 to 2023). The contribution of ATC subgroups to the retail sales structure was established. It was revealed that the share of combined drugs was not more than 15% in the total retail sales structure that did not comply with international recommendations on DM treatment.